1991
DOI: 10.1007/bf00317383
|View full text |Cite
|
Sign up to set email alerts
|

Leaf lifespan as a determinant of leaf structure and function among 23 amazonian tree species

Abstract: The relationships between resource availability, plant succession, and species' life history traits are often considered key to understanding variation among species and communities. Leaf lifespan is one trait important in this regard. We observed that leaf lifespan varies 30-fold among 23 species from natural and disturbed communities within a 1-km radius in the northern Amazon basin, near San Carlos de Rio Negro, Venezuela. Moreover, leaf lifespan was highly correlated with a number of important leaf structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
520
9
13

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(577 citation statements)
references
References 35 publications
35
520
9
13
Order By: Relevance
“…In this study, estimated values of leaf life span are consistent with those reported by Williams et al (1989), who observed that understory Piper species have leaf longevity greater than one year. Indeed, leaves with A mass of 62.2 nmol g −1 s −1 (this study) have leaf longevity of 15 (Reich et al, 1991) to 30 months (Poorter and Bongers, 2006), which suggests our leaf longevity estimate is rather conservative. In comparison with gap-demanding species, shade tolerant plants also have high LMA, leaves with a long life span, and synthetize large amount of antiherbivore metabolites (Valladares and Niinemets, 2008;Gommers et al, 2013).…”
Section: Leaf Structure-function Relationshipsmentioning
confidence: 72%
“…In this study, estimated values of leaf life span are consistent with those reported by Williams et al (1989), who observed that understory Piper species have leaf longevity greater than one year. Indeed, leaves with A mass of 62.2 nmol g −1 s −1 (this study) have leaf longevity of 15 (Reich et al, 1991) to 30 months (Poorter and Bongers, 2006), which suggests our leaf longevity estimate is rather conservative. In comparison with gap-demanding species, shade tolerant plants also have high LMA, leaves with a long life span, and synthetize large amount of antiherbivore metabolites (Valladares and Niinemets, 2008;Gommers et al, 2013).…”
Section: Leaf Structure-function Relationshipsmentioning
confidence: 72%
“…Low tissue mass density in leaves is associated with a high specific leaf area, large total leaf area and fast growth, on the one hand (Garnier, 1992 ;Ryser & Lambers, 1995 ;Meerts & Garnier, 1996 ;Ryser & Aeschlimann, 1999), and with short life span and high resource losses on the other (Schla$ pfer & Ryser, 1996 ;Ryser & Urbas, 2000). Leaf toughness and high tensile strength are associated with slow growth and also with a high degree of mechanical stability of the leaves, which tend to be well protected against environmental hazards such as herbivory (Coley, 1983 ;Reich et al, 1991 ;Cornelissen et al, 1999). Hence, tissue mass density is an effective means of predicting the performance of plants along gradients of resource availability (Wilson et al, 1999) ; a low tissue mass density is characteristic of plants of productive habitats, a high tissue mass density is typical in plants of unproductive environments Studies on the ecological significance of tissue structure have mostly been restricted to aboveground organs, especially leaves.…”
Section: mentioning
confidence: 99%
“…Extensive literature exists relating the physical properties of leaves to their ecology, covering topics such as herbivory (Coley, 1983 ;Raupp, 1985 ;Nichols-Orians & Shultz, 1990 ;Choong, 1996), decomposition (Arsuffi & Suberkropp, 1984 ;Gallardo & Merino, 1993), sclerophylly (Medina et al, 1990 ;Choong et al, 1992 ;Turner, 1994) and leaf longevity (Reich et al, 1991). Although fracture properties are measured routinely in engineering, determining the fracture properties of plants, and of biomaterials in general, is complicated for the following reasons.…”
Section: mentioning
confidence: 99%